PENGARUH LATIHAN AEROBIK TERHADAP PENINGKATAN PERSENTASE KADAR VO2 MAX PADA PEROKOK AKTIF MAHASISWA STIKES BAITURRAHIM JAMBI - Renni Hidayati Zein (Universitas Baiturrahim, 2017)
Introduction :Aerobic exercise is a form of exercise or exercise that in its use of energy uses the oxidative process in generating ATP as the basic energy for all cells. Aerobic exercise has an effect on the heart resistance of the lungs and so forth. Light to moderate activity is aerobic exercise. Aerobic exercise should be done with a frequency of 3-5 times per week with a duration of exercise 20-30 minutes each time the exercise. Methods : In the case of active smokers, physiotherapy is instrumental, among others, to maintain physical fitness, increase endurance and especially in increasing levels of VO2 max in the body. Objective to determine the difference of moderate and moderate intensity aerobic exercise effect on increasing percentage of VO2 max level in active smokerResult : Based on research objectives and data analysis results, the conclusions of this study are as follows from research conducted within 8 weeks starting from September to november 2015 in Stikes Baiturrahim Jambi on the influence of moderate intensity aerobic exercise and moderate intensity to VO2 max in active smoker Student Stikes Baiturrahim Conclusion : aerobic exercise of mild intensity and moderate intensity performed 4 times a week for 8 weeks with a duration of 30 minutes each time treatment can increase VO2 max in active smokers.